Complementary and Alternative Medicines - Fateme Ghaedi MSc; Mahlagha Dehghan PhD; Masoumeh Salari MSc; Akbar Sheikhrabori MSc (SAGE Publishing, 2017)
Prevalence of complementary and alternative medicines is increasing specially in patients with chronic diseases. Therefore, based on the high prevalence of chronic disorders, the present study aimed to determine complementary and alternative medicine usage frequency and its determinant factors. This was a cross-sectional study. Five hundred clients participated in the study by using convenience sampling. A 2-part questionnaire (including demographic form and researcher-created questionnaire) was used for studying the prevalence of using complementary and alternative medicine methods, and users' satisfaction. Findings showed that 75.4% of people used at least one complementary and alternative medicine method. Most of users consumed medicinal plants (69.4%). The most common reason of using a complementary and alternative medicine method was common cold (32.9%). The highest satisfaction belonged to massage (2.94 ± 0.74). The usage of complementary and alternative medicine was 3.22 times higher in people with academic educations when compared with illiterate people. Concerning the high usage of complementary and alternative medicine, it is necessary to train specialists in this field in order to offer such treatments in a safe manner. Also, outcomes of application of complementary and alternative medicine methods should be studied.